Effectiveness of post-acute care for patients with cerebral vascular disease in Taiwan between 2014 and 2023: a narrative synthesis - Wu, Cheng-Che; Wu, Chang-Cheng; Lin, Kuan-Chia (Frontiers in Rehabilitation Sciences, 2025)
ObjectivesTo explore the overall effectiveness of the Post-Acute Care-Cerebrovascular Diseases (PAC-CVD) program in Taiwan, which was implemented in 2014.Data sourcesA systematic search of databases, namely PubMed and Google Scholar, was conducted. Eligible studies published between Jan 2014 and June 2023 were included.Study selectionStudies included those that explored stroke care, involved post-acute care, were conducted in Taiwan, focused on an inpatient model of the PAC-CVD program, and had either a quantitative or qualitative design. In total, 23 articles were identified and included for narrative synthesis after complete examination.Data extractionMultiple observers independently extracted the research articles, with their objectives focused on topics such as patient outcomes, quality of care, the influence of referral systems, cost-effectiveness, or outcome prediction for the PAC-CVD program.Data synthesisThe PAC groups showed significantly better performance in most functional outcome, quality of care, and cost-effectiveness indicators than the non-PAC groups. Patients with intra-hospital referrals or in partner hospitals had better outcomes. Younger age, ischemic stroke, and better baseline condition, especially in balance function, were strong predictive factors for stroke prognosis in the PAC program.ConclusionsThe PAC-CVD program, implemented in Taiwan through the establishment of an integrated healthcare system and a change in payment systems, not only enhanced functional recovery and quality of life of acute stroke patients but also improved the quality of health care. The program also offered a more efficient and effective care model for acute stroke patients by reducing medical expenditures. However, the PAC program has also increased the workload of clinical healthcare professionals. The successful PAC-CVD implementation indicates the possibility of a standard rehabilitative care model for acute stroke patients, with expansion to other diseases or conditions possible after adjustments to the payment structure and workload.